(untitled) (Third Sector Social Economic Review, 2019)
While subsidies related to international trade contribute to competitive capacity of subsidy-benefiting companies, some type of subsidies granted may damage the rival companies located in countries which are unable to support their companies. For this reason, administered by the WTO, multilateral trading system has displayed a strong tenacity to dismantle or to minimize harmful subsidies. This article reveals, in a historical perspective, the direction to which countries’ trade policies have evolved through subsidies. Since GATT entered into force in 1948, developed countries have been gradually forbidden to give subsidies to the export of industrial products. These bans have been extended to the developing countries as well, with the introduction of the Agreement on Subsidies and Countervailing Duties in 1994 as a result of Uruguay Tour. Similarly, with the enactment of the Agreement on Agriculture in 1994, both agricultural domestic and export subsidies have been disciplined: Trade talks on minimization of the domestic subsidies potentially detrimental to competition are going on under the umbrella of WTO within the framework of Doha Development Agenda. Agricultural export subsidies were forbidden completely as of late 2018.